Consumer perception towards meat safety: confirmatory factor analysis - Abu, Mimi Liana; Radam, Alias; Yacob, Mohd Rusli (Faculty of Economics and Management, Universiti Putra Malaysia, 2010)
This study was conducted to analyze consumers’ perceptions on meat safety. The results indicate that the main determinants of consumer perceptions are government’s safety awareness, campaigns and health conscious. Therefore, from the practical standpoint, it suggests that responsible parties should focus their attention on the development of products that have attributes such as proper packaging, labelling and GMP guaranteed in order to increase positive perception of meat safety among customers.